E-government diffusion in Iran: a public sector employees' perspective. (1st January 2014) - Hashemkhani Zolfani, Sarfaraz; Sedaghat, Maedeh; Rad, Meysam Donyavi
Governments worldwide, since the 1990s, have launched projects with the mission to simplify delivery of services through electronic means (Torres et al., 2005). E-government is a breakthrough of communication and transaction between a government and its citizens or government and industries. The purpose of this paper is to identify the most salient factors that are currently influencing the development and diffusion of e-government in Iran as perceived by government employees involved in e-government service delivery. After studying previous researches, seven effective e-government diffusion indicators are selected for prioritising using fuzzy AHP and based on the experts' viewpoints who are the government employees involved in e-government service delivery. The findings reveal that accessibility, security and availability of public services are the first three most important criteria among citizens in relation to e-government adoption in Iran, respectively. This research strategy offers a new and more balanced perspective of e-government adoption and diffusion in Iran.